Uji Efektivitas Ekstrak Dekok Daun Namnam (Cynometra cauliflora L.) Terhadap Penurunan Kadar Gula Darah Pada Tikus Putih Jantan (Rattus norvegicus) Yang Diinduksi Aloksan. - Dede Komarudin; Reza Putri (IONTech Journal, 2021)
Namnam leaf (Cynometra cauliflora L.) is one of the plants that has medicinal properties. Various secondary metabolites, such as phenols and flavonoids, are thought to reduce blood glucose levels. The aim of this study was to determine the effectiveness of namnam leaf dekok extract (Cynometra cauliflora L.) on reducing blood sugar levels in male white rats (Rattus norvegicus) induced by alloxan. The study was an experimental study, using experiments on male white rats (Rattus norvegicus) using namnam leaf decoction extract (Cynometra cauliflora L.) and data obtained from measuring blood sugar using the microlab 200 levels were statistically analyzed using the One Way ANOVA SPSS 21 method to determine the existence the difference between the treatments. Based on the results obtained, it can be concluded that the extract of namnam leaf dekok (Cynometra cauliflora L.) has an effect in reducing blood sugar levels. The dose of namnam leaf dekok extract dose 3 showed the best reduction in blood sugar levels compared to dose 1 and dose 2. The most optimal dose was found at dose 3 namnam leaf dekok extract (Cynomtetra cauliflora L.). And based on the results of the study, the comparison drug used was metformin, and the dose that was almost as significant as the comparator drug was dose 3.